Microseismic Monitoring, Positioning Principle, and Sensor Layout Strategy of Rock Mass Engineering - Tianhui Ma; Daoyuan Lin; Chun’an Tang; Kedar Prasad Yadav; Zhiqiang Feng; Ke Ma (Geofluids)
Microseismic monitoring technology can start from the most initial stage of rock deformation and track and monitor the progressive failure process of rock mass from the fracture of rock blocks to the instability of rock mass. Thus, the scientific nature of monitoring work is greatly promoted, and the accuracy and advance of the prediction of engineering and geological disasters are improved. In this paper, the fracture and instability of rock can be analyzed by analyzing the microseismic signals produced by rock failure; The location of microseismic source can be determined by multipoint synchronous data acquisition to determine the time when each sensor (at least 5) receives microseismic signals; Combined with practical engineering experience for underground engineering in growth, heading tunnel, put forward only sensor arrangement to take mobile, follow the semienclosed layout network. We hope to give some reference to the researchers who are concerned with microseismic monitoring technology.